Dilemmas of growth: the Indian experience - "Dantwala, M. L." (New Delhi, 1996)
The 22 papers that constitute this volume contain the essence of the observations on the problems of growth and development by the leading Indian economist, M L Dantwala. The six parts of the book cover: values in economic thought; agricultural development and policy; planning for rural development; agricultural-price policy; rural credit; and agricultural labour and employment.
Keywords: India-Economic policy-1947